Use of Lisdexamfetamine to Treat Obesity in an Adolescent with Severe Obesity and Binge Eating - Gitanjali Srivastava; Valerie O'Hara; Nancy Browne (MDPI AG, 2019)
Approximately two-thirds of US children and adolescents have either obesity or overweight status, with almost 24% of adolescents (ages 12⁻19 years) afflicted with severe obesity, defined as >1.2 × the 95th BMI percentile for age/gender. Despite the increasing disproportionate rise in severe or extreme childhood obesity, many children in weight management programs do not achieve a healthy weight. Most often, these patients will go on to require metabolic and bariatric surgery (MBS), but challenges and limitations may prohibit MBS on adolescents. Thus, tertiary care pediatric weight management centers are compelled to treat select pediatric obesity subtypes presenting with disease progression and disability with the available adult FDA-approved therapeutic modalities, specifically pharmacotherapy, in order to alleviate the disease state and provide relief to the patient. Here, we describe a case of severe pediatric obesity where a dedicated multidisciplinary pediatric weight management team at a tertiary care center utilizes a progressive pharmacotherapeutic approach with enormous benefits to the patient, highlighting the urgent gap and clinical care needs of this special population niche of severe adolescent obesity.